Literature Study of Efforts to Settlement the Russia-Ukraine Dispute According to International Law - Syuryansyah, Syuryansyah; Amalia, Ridha (Jurnal Hubungan Internasional Indonesia, 2025)
This research focuses on the efforts to resolve the dispute between Russia and Ukraine based on international law. The method used in this study is a qualitative-descriptive approach, where the discussion on dispute resolution methods between the two countries is presented using descriptions based on facts found in the field. The data sources analyzed in this study come from various articles and news about resolving the Russia-Ukraine dispute. The analytical framework refers to the international dispute resolution law introduced by Huala Adolf to identify academics' efforts to resolve the Russia-Ukraine conflict. The findings of this research show that numerous efforts have been made to resolve the dispute between Russia and Ukraine, but until now, no comprehensive solution has been achieved.